Implementasi Pembelajaran Matematika Berbasis Virtual Reality untuk Pemahaman Konsep Siswa: Implementation of Virtual Reality-Based Mathematics Learning for Students' Conceptual Understanding - Novira Ramadhani Ginting; Laili Habibah Pasaribu; Eva Julyanti (ITScience (Information Technology and Science), 2026)
Learning mathematics, especially spatial figures, remains a challenge for students because it is abstract and often considered difficult. Therefore, innovative learning media are needed to improve students’ conceptual understanding, including Virtual Reality (VR). This study aims to determine the effect of implementing VR media on students’ conceptual understanding of spatial figures in mathematics. This study uses a quantitative approach with a Quasi-Experimental design of the Pretest-Posttest Control Group Design type. The sample consisted of two classes at SMP Negeri 5 Bilah Barat: the experimental and control classes, each with 29 students. Data were obtained through pre- and posttest measures and analyzed using normality, homogeneity, N-Gain, and paired-samples t-tests. The results showed that students’ conceptual understanding in the experimental class was higher than in the control class. The average score of the experimental class increased from 42.79 to 75.07, while the control class increased from 49.03 to 56.96. The N-Gain test showed an increase of 59.5% in the experimental class and 16.5% in the control class. The Paired Sample T-Test significance value of 0.000 (< 0.05) indicates a significant difference after the application of VR media. Virtual Reality (VR) learning media has a positive, quite effective effect on students’ understanding of mathematical concepts in spatial figures material.